Emerge of colorectal cancer in Lynch syndrome despite colonoscopy surveillance: a challenge of hide and seek - Helderman, Noah; van Leerdam, Monique E.; Kloor, Matthias; Ahadova, Aysel; Nielsen, Maartje (Critical reviews in oncology, hematology, 2024)
Even with colonoscopy surveillance, Lynch syndromes (LS) carriers still develop colorectal cancer (CRC). The cumulative incidence of CRCs under colonoscopy surveillance varies depending on the affected mismatch repair (MMR) gene. However, the precise mechanisms driving these epidemiological patterns remain incompletely understood. In recent years, several potential mechanisms explaining the occurrence of CRCs during colonoscopy surveillance have been proposed in individuals with and without LS. These encompass biological factors like concealed/accelerated carcinogenesis through a bypassed adenoma stage and accelerated progression from adenomas. Alongside these, various colonoscopy-related factors may contribute to formation of CRCs under colonoscopy surveillance, like missed yet detectable (pre)cancerous lesions, detected yet incompletely removed (pre)cancerous lesions, and colonoscopy-induced carcinogenesis due to tumor cell reimplantation. In this comprehensive literature update, we reviewed these potential factors and evaluated their relevance to each MMR group in an attempt to raise further awareness and stimulate research regarding this conflicting phenomenon.
Gesehen am 11.11.2024